Experimental study on web crippling of stainless steel built-up I-sections under interior-two-flange loading condition - Yasmin Binte Ibrahim (Nanyang Technological University, 2022)
This paper consists of an experimental study on the design of stainless-steel cold-formed built-up I-sections under web crippling failure. All of the test results and procedures used throughout the programme will also be listed in this paper. The built-up I-sections are made using two equal-sized C-channels which have been joined together and fastened with screws. A total of 14 built-up I-section members went through web crippling tests under the Interior-Two-Flange (ITF) loading condition. In this experimental study, the specimens have different screw arrangements, nominal heights, and nominal thickness to assess whether that will influence the overall performance of the built-up I-section. Specimens with different screw arrangements were similar in each loading condition and the specimens with screws located closest to the flange-web junctions tends to produce the maximum web-crippling resistances of the built-up I section. Due to the limited studies available on stainless steel built-up I-sections under the ITF web crippling condition, the obtained test results of the ultimate load (PT) and the theoretical ultimate loads (PEC3 , PAISI, PAS/NZS) have been obtained from the different steel design codes which are namely (i) Eurocode 3: Design of Steel Structures (EN 1993-1-3); (ii) North American Specification for the Design of Cold-Formed Steel Structural Members (AISI S100); (iii) New Zealand Standards (AS/NZS 4600). Based on the comparison against the existing design guidelines, the theoretical ultimate load PAS/NZS and the PEC3 appears to be unconservative. Therefore, further studies will have to be done to obtain a more accurate set of design codes.